Improving the Ability to Understand Anecdotal Text Concepts and Information using the Window Shopping Model - Madani, Tiara Surya; Wahyudi, Agus Budi; Leyla Aailyah (FITK UIN Walisongo Semarang, 2024)
ABSTRACTThis research aims to describe the results of applying and improving the ability to understand concepts and anecdotal text information in class XE4 students at SMA Negeri 5 Surakarta through the application of the window shopping model to anecdotal text material. The subjects in this research were 33 students in class XE4 of SMA Negeri 5 Surakarta. This research was carried out in two cycles with success indicators (1) The percentage of teacher and student activity increased above ≥ 80%, which is included in the very good criteria; (2) Test scores for the ability to understand concepts and anecdotal text information ≥ 70% of students scored ≥ 70; (3) through student responses to the application of the window shopping model ≥ 50%. The data collection technique applied in this research is observation and end-of-cycle test results. Observations were made on the activities of teachers and students when the cycle was implemented. The research results show that the window shopping model can improve the ability to understand concepts and anecdotal text information with learning steps, namely (1) initial activities, (2) core activities including organizing, discussing, conveying results, carrying out window shopping (going around to exchange information), evaluation, and apperception, as well as (3) final activities. This aspect of improvement can be seen from the results of observations of student and teacher activities, field notes, final test results for each cycle which have met the success criteria because they experienced an increase of 21.21%.